Is It a Puzzle to Estimate Econometric Models for The Turkish Economy? - Aysu Insel; Nedim Sualp (Turkish Economic Association, 2009)
This paper examines the roles and interrelationships among the main macroeconomic variables, namely the exchange rate, inflation rate, interest rate and real GDP in Turkey. It provides a descriptive data analysis in order to understand the behaviour of each variable and to explain the relationship between them. The data analysis has been performed considering the original and the decomposed variables over the five periods: 1987:01-2007:12; 1987:01-1994:03; 1994:04-2001:01; 2001:02-2007:12; and 2002:10-2007:12. Different lengths of the sample periods are selected for each variable covering the economic crises and different policy applications in order to compare the reasons and the consequences of different economic policy applications on these variables. It is concluded that the distribution of economic series is changing from one period to another. The contribution of this paper is to develop a base for econometric model construction for the Turkish economy all the way through their contemporaneous and causal relationship for different sub-sample periods.
Keywords: 330; Inflation rate; Exchange rate; Interest rate; Real GDP; Descriptive data analysis; Turkey; Ökonometrisches Makromodell; Türkei